Mismatch repair deficiency, chemotherapy and survival for resectable gastric cancer: an observational study from the German staR cohort and a meta-analysis$doriginal article : clinical oncology - Stolze, Thilo; Franke, Sabine; Haybäck, Johannes; Möhler, Markus; Grimminger, Peter; Lang, Hauke; Roth, Wilfried; Gockel, Ines; Kreuser, Nicole; Bläker, Hendrik; Wittekind, Christian; Lordick, Florian; et al. (Journal of cancer research and clinical oncology, 2023)
In a post hoc analysis of the MAGIC trial, patients with curatively resected gastric cancer (GC) and mismatch repair (MMR) deficiency (MMRd) had better median overall survival (OS) when treated with surgery alone but worse median OS when treated with additional chemotherapy. Further data are required to corroborate these findings.